Prenatal Gentle Yoga untuk Mengurangi Intensitas Nyeri Punggung pada Ibu Hamil - Linda Andri Mustofa (Universitas Faletehan, 2023)
Back pain was a problem complained by more than 50% of pregnant women. The complaint caused various effects ranging from mild discomfort to disturbance of pregnant women activities, affecting on the quality of life. This study aimed to determine the effectiveness of prenatal gentle yoga in reducing the intensity of back pain in pregnant women. The research design was quasi-experimental with a non-equivalent control group. The population was all third trimester pregnant women who experienced back pain at Denik and Dotyk Independent Midwife Practice. The sample size was 40 respondents who were selected by allocation random technique. The respondents were divided into 2 groups, namely 20 respondents in the intervention group and 20 respondents in the control group. The pain measurement used numerical rating scale (NRC). The data analysis used Mann Whitney statistical test. The result of data analysis showed that there was a significance; thus, the researchers concluded that prenatal gentle yoga could reduce back pain intensity of pregnant women (p1=0.005; p2=0.000; p3=0.027; p4=0.000). Prenatal gentle yoga is a movement that targets stiff, weak and untrained body parts to increase mobility, strength and posture impacting on reducing pain.